Vulnerability and resilience a conceptual framework applied to three asian countries Bhutan, Maldives, and Nepal. - Guillaumont, Patrick (South Asia working papers., 2017)
Three kinds of vulnerability have been considered for each country: economic, climatic, and political. Comparative assessment of countries is likewise undertaken using available and comparable indicators, e.g., economic vulnerability index and fragile state index. The assessment shows that each of the three countries seems the most vulnerable in one of the three dimensions of vulnerability: Bhutan for structural economic vulnerability, Maldives for physical vulnerability to climate change, and Nepal for state fragility.